2015
DOI: 10.1080/02643944.2015.1005657
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the ‘Safe’ concept in teaching: what can we learn from teachers’ understanding?

Abstract: 2The word 'safe' is widely used in everyday education speak in phrases such as 'safe learning environment' but how do trainee and experienced teachers interpret, understand and use this word in their everyday teaching? Teachers are acting as observers of pupils' wellbeing and one of their roles in the classroom is to offer support to build relationships and enable pupils to achieve their best. This case study reports the use of the 'safe' concept by trainee and experienced teachers in England and uses Boostrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The connection students feel with a group can positively or negatively affect their academic outcomes (Lee, Borden, Serido, & Perkins, 2009). Turner and Braine (2015) conducted a study of 32 teachers to determine whether there is a connection between safety and student performance. They found both novice and experienced teachers reported that students who felt safe submitted higher quality work.…”
Section: Student Readiness To Learnmentioning
confidence: 99%
“…The connection students feel with a group can positively or negatively affect their academic outcomes (Lee, Borden, Serido, & Perkins, 2009). Turner and Braine (2015) conducted a study of 32 teachers to determine whether there is a connection between safety and student performance. They found both novice and experienced teachers reported that students who felt safe submitted higher quality work.…”
Section: Student Readiness To Learnmentioning
confidence: 99%
“…That is to say a place, where they do not feel suffocated and bored. In line with these findings, a case study of experienced teachers and postgraduate trainee teachers on the concept of 'safe' in instruction by Turner and Braine (2015) indicated that respect and sense of comfort in the class contribute to a feeling of safety in students. Their findings indicated that students feel safe in a learning environment where they do not feel embarrassed, but confident enough to ask questions or share ideas.…”
Section: Expected Learning Atmospherementioning
confidence: 66%
“…A safe space has been defined by Holley and Steiner as a climate in which students feel safe expressing themselves openly and honestly, taking risks to explore the root of their views, beliefs, and opinions and in many cases confronting themselves and others [38]. This definition highlights that it is not the physical space that is safe or the catalyst for the experience of safety, rather it is a climate that is free from the potential for of psychological or emotional harm [15,[38][39][40][41]. It is a definition that highlights the educational contexts that have been found to foster intellectual and social learning for students [43].…”
Section: The Role Of Safe Spaces In Educationmentioning
confidence: 99%
“…Safe spaces are built upon mutual respect and promote healthy social interactions and an atmosphere for community building and academic success [38,39]. These learning environments recognize the connectedness between student well-being and their academic achievement [40] and seek to balance both presenting needs.…”
Section: The Role Of Safe Spaces In Educationmentioning
confidence: 99%